Problems of integration theory in relation to the developing countries - Sefik Alp Bahadir (Intereconomics, 1978)
The opportunities for the integration of developing countries and the limitations to such integration have not received enough attention in the scientific discussion on the reform of the international economic order, with the result that a considerable research backlog has been accumulating in this field. The following article shows that the established integration theory which has been evolved primarily with the problems of the European integration movement in mind is not able to evolve adequate criteria for decisions on integrations of developing countries.
Keywords: 330; Integration